1996
DOI: 10.1172/jci118692
|View full text |Cite
|
Sign up to set email alerts
|

Elafin, a serine elastase inhibitor, attenuates post-cardiac transplant coronary arteriopathy and reduces myocardial necrosis in rabbits afer heterotopic cardiac transplantation.

Abstract: We have related experimentally induced post-cardiac transplant coronary arteriopathy to increased elastolytic activity, IL-1 ␤ , fibronectin-mediated inflammatory and smooth muscle cell (SMC) migration, and SMC proliferation. Since our in vitro studies show that a serine elastase releases SMC mitogens and facilitates IL-1 ␤ induction of fibronectin, we hypothesized that administration in vivo of the specific serine elastase inhibitor, elafin, would decrease the post-cardiac transplant coronary arteriopathy. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 77 publications
1
42
0
Order By: Relevance
“…It is noteworthy that both of these anti-inflammatory actions were associated with reduced activation of the transcription factor NF-B and concomitant increase in IB␣ protein. Our findings extend the observed potential of elafin augmentation in models of arterial wall inflammation, including vein graft degeneration (16) and transplant arteriosclerosis (17). They indicate that gene augmentation of both elafin and mSLPI may have therapeutic potential in the treatment of atherosclerosis.…”
supporting
confidence: 80%
“…It is noteworthy that both of these anti-inflammatory actions were associated with reduced activation of the transcription factor NF-B and concomitant increase in IB␣ protein. Our findings extend the observed potential of elafin augmentation in models of arterial wall inflammation, including vein graft degeneration (16) and transplant arteriosclerosis (17). They indicate that gene augmentation of both elafin and mSLPI may have therapeutic potential in the treatment of atherosclerosis.…”
supporting
confidence: 80%
“…28 The FLAG-elafin was conjugated to a FLAG affinity column using a FLAG-tagged protein immunopreciptation kit (Sigma). Protein extracts were prepared as described above for the elastase activity assays, using lungs of S100A4 mice 7 days after inoculation with M1-MHV-68.…”
Section: Purification Of Elafin-bound Elastasementioning
confidence: 99%
“…opathy after transplantation, 28,51 vein graft atherosclerosis 52 and fibrosis following viral myocarditis, 53,54 or pulmonary hypertension induced by hypoxia 12,14 or monocrotaline. 13,15 In five of these models, 28,50,52,54 elafin was used as the elastase inhibitor, given as an infusion, 28 by gene therapy 50,52 or in an overexpressing transgenic mouse.…”
Section: Grade Imentioning
confidence: 99%
See 1 more Smart Citation
“…Some have reported that ␣ 1 -antitrypsin inhibits granzyme B (17), while we (C.E.H., unpublished observations) and others (P. Bird, personal communication) have not observed such inhibition. Since elafin suppresses by 75% the degradation of insoluble elastin by purified peripheral blood T cells (18), and granzyme A is elastolytic (19), it has been suggested that elafin inhibits granzyme A (18). To our knowledge, there are no data available on granzyme inhibition by SLPI.…”
mentioning
confidence: 99%